Woyzeck - Büchner, Georg,Thorne, Jack (Nick Hern Books, 2017)
1980s Berlin. The Cold War rages and the world sits at a crossroads between Capitalism and Communism. On the border between East and West, a soldier and his lover are trying to build a future for their child. But the cost of escaping poverty is high, and its tragic consequences unfold in this tale of the people society leaves behind
Keywords: Soldiers